HIF-1α affects sensitivity of murine squamous cell carcinoma to boron neutron capture therapy with BPA. (3rd October 2021) - Sanada, Yu; Takata, Takushi; Tanaka, Hiroki; Sakurai, Yoshinori; Watanabe, Tsubasa; Suzuki, Minoru; Masunaga, Shin-ichiro
Abstract: Purpose To examine whether hypoxia and Hif-1α affect sensitivity of murine squamous cell carcinoma cells to boron neutron capture therapy (BNCT). Materials and methods SCC VII and SCC VII Hif-1α-deficient mouse tumor cells were incubated under normoxic or hypoxic conditions, and cell survival after BNCT was assessed. The intracellular concentration of the 10 B-carrier, boronophenylalanine- 10 B (BPA), was estimated using an autoradiography technique. The expression profile of SLC7A5, which is involved in the uptake of BPA, and the amount of DNA damage caused by BNCT with BPA were examined. A cell survival assay was performed on cell suspensions prepared from tumor-bearing mice. Results Hypoxia ameliorated SCC VII cell survival after neutron irradiation with BPA, but not BSH. Hypoxia-treated SCC VII cells showed decreased intracellular concentrations of BPA and the down-regulated expression of the SLC7A5 protein. BPA uptake and the SLC7A5 protein were not decreased in hypoxia-treated Hif-1α-deficient cells, the survival of which was lower than that of SCC VII cells. More DNA damage was induced in SCC VII Hif-1α-deficient cells than in SCC VII cells. In experiments using tumor-bearing mice, the survival of SCC VII Hif-1α-deficient cells was lower than that of SCC VII cells. Conclusion . Hypoxia may decrease the effects of BNCT with BPA, whereas the disruption of Hif-1α enhanced sensitivity to BNCT with BPA.